The anatomy of type : a graphic guide to 100 typefaces - Coles, L. Stephen (New York : Harper Design, 2012)
The Anatomy of Type is the ultimate stylistic guide to the intricacies and design of 100 indispensable typefaces. A delightful, colorful, and visual reference guide created by Stephen Coles and Tony Seddon---two acknowledged pros in the font design world---The Anatomy of Type was developed with typographers, graphic designers, and font geeks in mind, graphically and visually expanding on the current font-mania initiated by Simon Garfields's Just My Type.
The Anatomy of Type explores one hundred traditional and modern typefaces in loving detail, with a full spread devoted to each entry. The full character set from each typeface is shown, and the best letters for identification are enlarged and annotated, revealing key features, anatomical details, and the finer, often-overlooked elements of type design. Containing in-depth information on everything from the designer and foundry, the year of release, and the different weights and styles available, The Anatomy of Type is more than a reference guide to the intricacies of typeface design. It is a visual send-up of some of the world's most beloved typefaces, whimsically displayed in vibrant color.
-- Foreword -- Introduction -- How to use this book -- Glossary of typographic terminology -- The anatomy of type -- Type classification at a glance -- Key classifications features -- Humanist Serif -- Transitional Serif -- Rational Serif -- Contemporary Serif -- Inscribed/ Engraved -- Grotesque Sans -- Neo-Grotesque Sans -- Gothic Sans -- Geometric Sans -- Humanist Sans -- Neo-Humanist Sans -- Grotesque Slab -- Geometric Slab -- Humanist Slab -- Script -- Display.
Includes index.
Keywords: Type and type-founding -- History; Type and type-founding -- Specimens; Printing -- History